Exploring apoplast reorganization in the nodules of Lotus corniculatus L. growing on old Zn-Pb calamine wastes - Sujkowska-Rybkowska, Marzena (Journal of plant physiology, 2022)
Copyright © 2021 Elsevier GmbH. All rights reserved.